Proteolysis assessment in isolated Plasmodium falciparum living cells at the asexual blood stages - Rojas, Laritza; Budu, Alexandre; El Chamy Maluf, Sarah; Melo, Pollyana S.; Gomes Smaul, Mayrim M.; K. Carmona, Adriana; Gazarini, Marcos L.; Alonso del Rivero, Maday (Revista Cubana de Medicina Tropical, 2018)
It has been demonstrated that proteases play crucial roles in Plasmodium falciparum infection and therefore have been considered as targets for the development of new therapeutic drugs. The aim of this study was to describe the specific proteolytic activity profile in all blood stages of P. falciparum isolated parasites in order to explore new antimalarial options. For this purpose, we used the fluorogenic substrate Z-Phe-Arg-MCA (Z: carbobenzoxy, MCA: 7-amino-4-methyl coumarine) and classic inhibitors for the different classes of proteolytic enzymes, such as phenylmethylsulfonyl fluoride (PMSF), 1.10-phenantroline, pepstatin A and E64 to study the inhibition profiles. As expected, due to the high metabolic activity in mature stages, the substrate was mostly degraded in the trophozoite and schizont, with specific activities ~ 20 times higher than in early stages (merozoite/rings). The major actors in substrate hydrolysis were cysteine proteases, as confirmed by the complete hydrolysis inhibition with E64 addition. Proteolytic activity was also inhibited in the presence of PMSF in all but the schizont stage. However, PMSF inhibition was the result of unspecific interaction with cysteine proteases as demonstrated by reversion of inhibition by dithiotreitol (DTT), indicating that serine protease activity is very low or null. To our knowledge, this is the first report aiming to describe the proteolytic profile of P. falciparum isolated parasites at all the erythrocytic cycle stages. The results and protocol described herein can be useful in the elucidation of stage specific action of proteolysis-inhibiting drugs and aid in the development of antimalarial compounds with protease inhibitory activity.